Financing water supply and sanitation investments : - Baietti, Aldo (2005)
More than 1.1 billion people worldwide do not have access to safe drinking water and 2.4 billion lack adequate sanitation facilities. Even in many countries with water supply systems, piped water is often intermittent and unsafe for drinking. Sanitation facilities are frequently inadequate or in disrepair. It is particularly difficult to attract private investment for water and sanitation projects, mainly because the water sector is subject to risks which include high capital intensity, political pressure on tariffs, deficient regulation, subsovereign risk and limited access to financing, insufficient knowledge of networks, and currency mismatch between revenues and financing sources. International financial institutions (IFIs) offer a number of risk mitigation instruments designed to reduce the risks that investors confront in doing business in developing countries, which are examined in this paper (financed by the Government of the Netherlands through the Bank-Netherlands Partnership Program (BNPP)). One of these measures is output-based aid, in which a government provides subsidies during the implementation phase of a project and links them to the operator’s performance. IFIs can also play a role in increasing local financial market access for private water projects. They can also help the government shield water infrastructure enterprises from severe macro and currency shocks through liquidity support.